Effect of maternal obesity on fetal and postnatal baboon (Papio species) early life phenotype. Issue 2 (20th December 2018) - Li, Cun; Jenkins, Susan; Considine, McKenna M.; Cox, Laura A.; Gerow, Kenneth G.; Huber, Hillary F.; Nathanielsz, Peter W.
Abstract: Background: Non‐human primate models of developmental programming by maternal obesity (MO) are needed for translation to human programming outcomes. We present baboon offspring (F1) morphometry, blood cortisol, and adrenocorticotropic hormone (ACTH) from 0.9 gestation to 0‐2 years. Methods: Control mothers ate chow; MO mothers ate high‐fat high‐energy diet pre‐pregnancy through lactation. Results: Maternal obesity mothers weighed more than controls pre‐pregnancy. Maternal obesity gestational weight gain was lower with no correlation with fetal or placenta weights. At 0.9 gestation, MO and control F1 morphometry and ACTH were similar. MO‐F1 0.9 gestation male cortisol was lower, rising slower from 0‐2 years vs control‐F1. At birth, male MO‐F1 and control‐F1 weights were similar, but growth from 0‐2 years was steeper in MO‐F1; newborn female MO‐F1 weighed more than control‐F1 but growth from 0‐2 years was similar. ACTH did not change in either sex. Conclusions: Maternal obesity produced sexually dimorphic fetal and postnatal growth and hormonal phenotypes.